PENGEMBANGAN MODUL PENGANTAR EKONOMI BERBASIS KOMPETENSI UNTUK SISWA SMK - YS Sri Retno Winarni; Pargito Pargito; Raden Gunawan Sudarmanto (Faculty of Teacher Training and Education, University of Lampung, 2014)
The aims of research are to produce an introductory to economic module competency based at tenth grade of SMK which is interesting and feasible used in learning, and to find out the effectiveness of module in increasing student competency. Design of research used design (R D). Design of learning development follows steps Dick and Carey. To know the effectiveness product was done by Experiment Model Test Pretest – Pos test (Control Group Design). The result of development research can conclude: 1) the result of expert assessment matter, design expert, student and teacher product can be said to be feasible (2) according to result of product t-test can be said that module is very effective in improving student competency. The effectiveness was tested by using t-test was gotten t-test coefficient is higher than t- table coefficient (3,759 1,997), it means introductory to economic module learning is very effective.Penelitian ini bertujuan untuk menghasilkan modul pengantar ekonomi berbasis kompetensi Siswa SMK Kelas X yang menarik dan layak digunakan dalam pembelajaran, dan mengetahui efektifitas modul dalam meningkatkan kompetensi siswa. Desain penelitian menggunakan RD. Desain pengembangan pembelajaran mengikuti langkah-langkah Dick and Carey. Untuk mengetahui efektifitas produk dilakukan dengan Uji Eksperimen Model Pretest-Postest (Control Group Design). Hasil pengembangan dapat disimpulkan: (1) Hasil penilaian ahli materi, ahli desain, siswa dan guru produk dapat dikatakan layak digunakan (2) Berdasarkan hasil uji coba produk dapat dikatakan bahwa Modul efektif digunakan untuk meningkatkan kompetensi siswa. Efektifitas diuji dengan menggunakan uji-t diperoleh koefisien t hitung lebih besar dari koefisien t table (3,7591,997), dengan demikian pembelajaran menggunakan modul pengantar ekonomi dinyatakan lebih efektif.Kata kunci: berbasis kompetensi, modul, pengantar ekonomi, pengembangan